2017
DOI: 10.1371/journal.pone.0187672
|View full text |Cite
|
Sign up to set email alerts
|

Central conduction time in auditory brainstem response and ear advantage in dichotic listening across menstrual cycle

Abstract: The ovarian hormones fluctuate during the menstrual cycle in women. Such fluctuation of sex hormones, in particular estrogen, is believed to affect the central conduction time in auditory function as well as the language lateralization in cognitive function. However, findings are inconsistent. The underlying mechanisms are also unclear. This paper examined if there was any relation between the central conduction time and the language lateralization at different times during the menstrual cycle. Twenty young wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(17 citation statements)
references
References 28 publications
1
16
0
Order By: Relevance
“…For example, Batta et al [18] reported significantly shorter latencies of auditory brainstem evoked responses when their participants were tested during the days of their menstrual cycles after ovulation. In contrast, Hu and Lau [14] reported longer latency times when their participants were tested during this same portion of the menstrual cycle.…”
Section: Introductionmentioning
confidence: 91%
See 4 more Smart Citations
“…For example, Batta et al [18] reported significantly shorter latencies of auditory brainstem evoked responses when their participants were tested during the days of their menstrual cycles after ovulation. In contrast, Hu and Lau [14] reported longer latency times when their participants were tested during this same portion of the menstrual cycle.…”
Section: Introductionmentioning
confidence: 91%
“…They found a lower REA in dichotic listening responses for the forced left ear condition measured during the pre-ovulation portion of the menstrual cycle. This increase in lateralization toward the left side coincided with longer brainstem response latencies for peak V of the auditory signals [14]. In contrast, other researchers reported that higher levels of estradiol were associated with lower lateralization scores across all dichotic listening conditions [11, 13].…”
Section: Introductionmentioning
confidence: 98%
See 3 more Smart Citations